Dysregulated Inflammation During Obesity: Driving Disease Severity in Influenza Virus and SARS-CoV-2 Infections - Hulme, Katina D.; Noye, Ellesandra C.; Short, Kirsty R.; Labzin, Larisa I. (Frontiers in Immunology, 2021)
AAcute inflammation is a critical host defense response during viral infection. When dysregulated, inflammation drives immunopathology and tissue damage. Excessive, damaging inflammation is a hallmark of both pandemic influenza A virus (IAV) infections and Severe Acute Respiratory Syndrome -Coronavirus-2 (SARS-CoV-2) infections. Chronic, low-grade inflammation is also a feature of obesity. In recent years, obesity has been recognized as a growing pandemic with significant mortality and associated costs. Obesity is also an independent risk factor for increased disease severity and death during both IAV and SARS-CoV-2 infection. This review focuses on the effect of obesity on the inflammatory response in the context of viral respiratory infections and how this leads to increased viral pathology. Here, we will review the fundamentals of inflammation, how it is initiated in IAV and SARS-CoV-2 infection and its link to disease severity. We will examine how obesity drives chronic inflammation and trained immunity and how these impact the immune response to IAV and SARS-CoV-2. Finally, we review both medical and non-medical interventions for obesity, how they impact on the inflammatory response and how they could be used to prevent disease severity in obese patients. As projections of global obesity numbers show no sign of slowing down, future pandemic preparedness will require us to consider the metabolic health of the population. Furthermore, if weight-loss alone is insufficient to reduce the risk of increased respiratory virus-related mortality, closer attention must be paid to a patient’s history of health, and new therapeutic options identified.